Pliensbachian ammonites from Southern Vendée (France). Toward the individualization of an Atlantic paleobiogeographic region - Fauré, Philippe; Bohain, Patrick (Comptes Rendus. Géoscience, 2022)
The Lower Pliensbachian series (Ibex Chronozone) of Southern Vendée (France) contains a unique mix of ammonites, with several Polymorphitidae, Uptonia atlantica [Fauré and Bohain, 2017], and Dayiceras dayiceroides [Mouterde, 1951], whose distribution till date seemed restricted to the Lusitanian Basin. As in Portugal, these taxa extend the linear evolutionary sequence of this family during the Masseanum and Valdani Subchronozones. Their discovery in Vendée enables qualifying the importance of the Lusitanian endemism. It allows integrating the Lusitanian Basin and Vendée, which paleogeographic reconstructions place closer, into the same Atlantic paleobiogeographic area. It can be extended to the western borders of the North-West European Bioprovince. During the Late Pliensbachian, it is probably through a diffusion within this paleogeographic area that the Tethyan taxa, which are very numerous in Portugal, would have reached Vendée and Western Europe in successive waves. It seems that this atlantic communication route was privileged, at least until the Early Toarcian.